Clubroot Disease Stimulates Early Steps of Phloem Differentiation and Recruits SWEET Sucrose Transporters within Developing Galls. Issue 12 (9th November 2018) - Walerowski, Piotr; Gündel, André; Yahaya, Nazariyah; Truman, William; Sobczak, Mirosław; Olszak, Marcin; Rolfe, Stephen; Borisjuk, Ljudmilla; Malinowski, Robert
Abstract : Plasmodiophora brassicae stimulates phloem differentiation and expression of phloem-specific SWEET transporters to hijack host metabolism. Abstract: Successful biotrophic plant pathogens can divert host nutrition toward infection sites. Here we describe how the protist Plasmodiophora brassicae establishes a long-term feeding relationship with its host by stimulating phloem differentiation and phloem-specific expression of sugar transporters within developing galls. Development of galls in infected Arabidopsis ( Arabidopsis thaliana ) plants is accompanied by stimulation of host BREVIS RADIX, COTYLEDON VASCULAR PATTERN, and OCTOPUS gene expression leading to an increase in phloem complexity. We characterized how the arrest of this developmental reprogramming influences both the host and the invading pathogen. Furthermore, we found that infection leads to phloem-specific accumulation of SUGARS WILL EVENTUALLY BE EXPORTED TRANSPORTERS11 and 12 facilitating local distribution of sugars toward the pathogen. Utilizing Fourier-transform infrared microspectroscopy to monitor spatial distribution of carbohydrates, we found that infection leads to the formation of a strong physiological sink at the site of infection. High resolution metabolic and structural imaging of sucrose distributions revealed that sweet11 sweet12 double mutants are impaired in sugar transport toward the pathogen, delaying disease progression. This work highlights the importance of precise regulation of sugar partitioning for plant–pathogen interactions and the dependence of P . brassicae 's performance on its capacity to induce a phloem sink at the feeding site.